A precessing magnetar model for GLEAM-X J162759.5-523504.3 - Ekşi, K. Yavuz; Şaşmaz, Sinem (arXiv, 2022)
We propose a precessing transient magnetar model for the recently discovered radio source GLEAM-X J162759.5-523504.3. We identify the observed period of $\sim 1$ ks as the precession period of the magnetar deformed due to its strong ($B_ \sim 10^{16}$ G) toroidal field. The resulting deformation of order $10^{-4}$ implies a spin period of $P_{\rm s} = 0.1$ s. Assuming a strong dipole field of $B_{\rm d} \sim 10^{14}$ G we predict a period derivative of $\dot{P}_{\rm s}\sim 10^{-11}$ s/s. We also predict that the precession period of the magnetar can be observed in the hard X-ray band just as the other three galactic magnetars exhibit precession.

3 pages, 1 figure
Keywords: High Energy Astrophysical Phenomena (astro-ph.HE); FOS: Physical sciences; Astrophysics - High Energy Astrophysical Phenomena